Mechanical upcycling immiscible polyethylene terephthalate-polypropylene blends with carbon fibre reinforcement - Gaduan,A; Singkronart,K; Bell,C; Tierney,E; Burgstaller,C; Lee,K-Y (ACS Applied Polymer Materials, 2022)
Ineffective sorting of post-consumer plastics remains one of the major obstacles in the recycling of plastics. Consequently, these highly heterogeneous, mixed post-consumer plastics will end up in landfill or have to be incinerated as repurposing them directly would lead to a polymer blend with inferior quality for many end-uses. In this work, we demonstrate the use of carbon fibers (CFs) to practically upgrade the mechanical properties of mixed plastics, adding value to them. This will create a stronger demand for mixed plastics to be used in various engineering applications. Using polyethylene terephthalate (PET) and polypropylene (PP) as the model immiscible polymer blend, we showed that the incorporation of CFs increased the tensile, flexural, and single-edge notched fracture toughness of the resulting CF-reinforced PET/PP composite blends. Despite the high environmental burden associated with the production of CFs, cradle-to-grave life-cycle analysis showed that CF-reinforced PET/PP composites have a lower environmental impact than the life-cycle scenarios of “doing nothing” and repurposing immiscible PET/PP blends as it is without CF reinforcement. This can be attributed to the weight saving achieved, a direct result of their higher mechanical performance. Our work opens up opportunities for the use of mixed plastics in various higher value applications such that they can be diverted away from landfill or incineration, in line with the concept of circular economy.